#BodyPositive? A critical exploration of the body positive movement within physical cultures taking an intersectionality approach - Griffin, Meridith; Bailey, K. Alysse; Lopez, Kimberly J. (Frontiers in Sports and Active Living, 2022)
Feminist activists and critical sport scholars in the global north have advocated for more inclusive representation of bodies and more accessible physical cultures. Body positivity, a contentious movement and concept, has been taken up in various ways by different groups. Some scholars believe it holds power to liberate individuals from patriarchal, neoliberal, capitalist, and colonial ideologies of what constitutes a “good” body. On the contrary, critics assert this movement has been gentrified by white-centered politics. Intersectionality has a similar genealogy as body positivity, with a rich history in Black feminist thought but now considered by many as coopted and whitened. In this article, we trace the rich and divergent legacies of both movements and explore at the structural level how body positivity is represented within physical cultures on Instagram. We use a social-justice oriented intersectionality framework exploring #BodyPositivity and #BodyPositive across a total of 141 posts using reflexive thematic analysis. We organize our findings into four themes: 1) Disclosure-Privilege of Body-Related Journeys; 2) The Absent-Present; 3) Consuming Positivity; and 4) Disrupting Normative Body Positivity Posts. Overall, we found that only certain bodies (and transformations) were visible within the data: those of (now) lean, white, cis-gendered individuals, many of whom were engaged in bodybuilding, and who were sharing their bodily transformation. We observe a remarkable absence of BIPOC, 2S LGBTQAI+, fat/thick/thicc/curvy, older, gender-nonconforming, and/or disabled representations. We also note the myriad ways that body positivity has been commodified and packaged into a product or service for consumption. Lastly, we outline and celebrate the exceptions to this norm where a minority of posts align more closely with the original intentions of the body positivity movement. We conclude with our position on how to do intersectionality research, and call on researchers to honor Black feminist origins and rich social justice history in these movements.